Mental health shame, self‐compassion and sleep in UK nursing students: Complete mediation of self‐compassion in sleep and mental health. Issue 3 (23rd December 2020) - Kotera, Yasuhiro; Cockerill, Vicky; Chircop, James G. E.; Forman, Dawn
Abstract: Aims: To explore relationships between mental health problems, mental health shame, self‐compassion and average length of sleep in UK nursing students. The increasing mental health problems in nursing students may be related to a strong sense of shame they experience for having a mental health problem. Self‐compassion has been identified as a protective factor for mental health and shame in other student populations. Further, studies highlight the importance of sleep relating to mental health. Design: A cross‐sectional design. Methods: A convenient sampling of 182 nursing students at a university in the East Midlands completed a paper‐based questionnaire regarding these four constructs, from February to April 2019. Correlation, regression and mediation analyses were conducted. Results: Mental health problems were positively related to shame and negatively related to self‐compassion and sleep. Mental health shame positively predicted and self‐compassion negatively predicted mental health problems: sleep was not a significant predictor of mental health problems. Lastly, self‐compassion completely mediated the impacts of sleep on mental health problems (negative relationship between mental health problems and sleep was fully explained by self‐compassion). Conclusion: The importance of self‐compassion was highlighted as it can reduce mental health problems and shame. Self‐compassion can protect nursing students from mental distress when they are sleep deprived. Impact: Nurses and nursing students are required to work irregular hours (e.g. COVID‐19) and mental distress can cause serious consequences in clinical practice. Our findings suggest that nurturing self‐compassion can protect their mental health and the negative impacts of sleep deprivation on mental health.